Overview and Impact of Attending Training Program on “Functional Ways of Working with Cerebral Palsy Child in Low-resource Setting” - Newaz, Fatema; Nuery, Nuzhat; Chakrabarty, Shohag; Islam, Ashik Ul; Uddin, Taslim (KYAMC Journal, 2025)
Background: There is a lack of available services including rehabilitation intervention for children with physical disability living in rural Bangladesh. Rehabilitation in Bangladesh is not a health priority and rehabilitation teamwork has been reported to have multiple challenges including few trained rehabilitation workforce, poor inter-specialty relationships, and scarcity of assisted devices for rehabilitation. Objective: To provide a comprehensive overview of the training program and assess the knowledge and skills acquired by trainees in developing countries. Additionally, to investigate potential strategies for moving forward and planning the effective implementation. Materials and Methods: Six days training was designed by Enablement Nepal with ice-breaking session, experience sharing, group working and presentation by participant, game of life played by participant, CBR establishment and ICF implementation, group work regarding CP child examination, goal set up, home visit, environmental barriers detection of that child in school and family and proposed solution. About twelve participants of different professional like physiatrist, physiotherapist, occupational therapist, rehabilitation facilitator, social worker, CBR worker attended six days interactive classes, group-works, home visit, field visit under supervision of instructor. Pre-training evaluation sheet and after-work questionnaire reveals thought differences of participant. Result: The outcomes of the training reflected a dynamic and continuous learning process. Participants, driven by their interests and diverse perspectives, actively took part in the training sessions. After the program, participants expressed a range of opinions and reactions concerning the training methods and their potential implementation. The mixed expressions highlighted the varied experiences and perspectives brought by the trainees. Conclusion: The participants acknowledged that similar training initiatives would further enhance their understanding and broaden their perspectives regarding functional rehabilitation. This underscores the importance of continuous training and collaborative efforts to address the challenges associated with caring for children with CP in low-resource settings. KYAMC Journal Vol. 15, No. 04, January 2025: 173-177